1997
DOI: 10.1007/s004210050308
|View full text |Cite
|
Sign up to set email alerts
|

Gender comparison of peak oxygen uptake: repetitive box lifting versus treadmill running

Abstract: The gender differences in peak oxygen uptake (VO2peak) for various modes of exercise have been examined previously; however, no direct gender comparisons have been made during repetitive lifting (RL). In the present study the VO2peak between RL and treadmill running (TR) was compared between 20 men [mean (SD) age, height, body mass and body fat: 21 (3) years, 1.79 (0.06) m, 81 (9) kg, 19 (6)%, respectively] and 20 women [mean (SD) age, height, body mass and body fat: 21 (3) years, 1.63 (0.05) m, 60 (7) kg, 27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
4
10
0
Order By: Relevance
“…The magnitude of this gender dierence is consistent with that reported in the literature for healthy subjects in this age group during treadmill running (Nindl et al 1998;Sparling 1980). It should be noted, however, that the actual values of the O 2 max were higher than that expected for Canadians of comparable age and could have some implications in the interpretation of the ®ndings of this study (Canadian Society for Exercise Physiology 1996).…”
Section: Gender Dierences In the Physiological Characteristics Of Subsupporting
confidence: 78%
“…The magnitude of this gender dierence is consistent with that reported in the literature for healthy subjects in this age group during treadmill running (Nindl et al 1998;Sparling 1980). It should be noted, however, that the actual values of the O 2 max were higher than that expected for Canadians of comparable age and could have some implications in the interpretation of the ®ndings of this study (Canadian Society for Exercise Physiology 1996).…”
Section: Gender Dierences In the Physiological Characteristics Of Subsupporting
confidence: 78%
“…In previous studies, it has been frequently reported that gender does not affect HR at AT or during maximal exercise in young people, whereas the results of studies about the effect of gender on minute ventilation at AT and maximal exercise have been conflicting (Younis et al 1990;Ogawa et al 1992;Helgerud 1994;Rickli et al 1997;Nindl et al 1998). In the present study, it was demonstrated, for the first time, that ventilatory and HR responses at the onset of voluntary exercise and passive movement did not differ between women and men.…”
Section: Gender Differencementioning
confidence: 94%
“…Jones et al (1999) reported that gender appeared to influence sympathetic and cardiovascular responses to various conditions (10, 12, 50%) of inspired oxygen levels. There have also been many studies about the effect of gender on minute ventilation and heart rate (HR) at the anaerobic threshold (AT) or at peak exercise in young people (Younis et al 1990;Ogawa et al 1992;Helgerud 1994;Rickli et al 1997;Nindl et al 1998). According to the results of those studies, while no gender effect seems to exist for HR at AT or peak levels of exercise, a male-female comparison of minute ventilation has been reported with various results.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the worker's performance using traditional aerobic protocols alone (on either a treadmill, cycle, or arm ergometer) instead of task-specific maximal or submaximal aerobic protocols, may or may not identify the individual's true physical capacity (McConnell et al 1984;Khalil et al 1985;Sharp et al 1988;Waters et al 1993;Nindl et al 1998;Bilzon et al 2001Bilzon et al , 2002. Compared to the standardized ergometric protocols, these authors argued that there is considerable variation in human performance in the tasks (e.g., lifting, lowering, pushing, pulling, carrying, etc.)…”
Section: Introductionmentioning
confidence: 97%